Análise cromatográfica e eletroforética de fármacos em suplementos alimentares e avaliação de interações medicamentosas in silico - Müller, Larissa Sabo (2018)
The increased demand for dietary supplements in recent years leads to an alarming scenario regarding the efficacy and safety of these products. The lack of a specific category for registration of these products leads to the practice of adulteration them with synthetic drugs, which would provide a better effectiveness in a short period of time. Still, the number of patients consuming supplements concomitantly with synthetic drugs has increased greatly in recent years, which can cause serious interactions. This association may be responsible for cases of unexpected therapeutic failure or side effects, as well as indirect health risks, which occur when the patient uses the supplement for therapeutic purposes despite the lack of evidence of benefits. This work describes the development of two analytical methods for the determination of 10 drugs (fluoxetine, paroxetine, caffeine, synephrine, phenolphthalein, amfepramone, amiloride, chlorthalidone, hydrochlorothiazide and furosemide) in 114 samples of dietary supplements marketed in Brazil. The first method, using capillary zone electrophoresis (CZE) with UV and C4D detection simultaneously allows the simultaneous determination of antidepressants, laxative, anorectic and diuretics under optimized conditions: working electrolyte 20 mmol L-1 phosphate buffer (pH 9.2) containing methanol 30% (v / v), separation potential -15 kV, temperature 25 ° C; hydrodynamic injection by gravity at 20 cm for 60 s. The method was validated in the parameters of linearity, limit of detection, limit of quantification, precision and accuracy. The method was able to identify the adulterants present in the samples with high selectivity and sensitivity. The second method employing HPLC with pulsed amperometric detection allows the detection of stimulants and diuretics under the following conditions: mobile phase phosphate buffer 5 mmol L-1 (pH 4.5) containing SDS 0.3 mmol L-1 and 50% methanol v / v); C18 column; sampling potential of + 0.8V; cleaning potentials of -0.2V and + 1.0V; flow rate of 1.0 mL / min. Also, a simulation was performed using an in silico model to predict drug interaction between sertraline and caffeine and sertraline and sildenafil. The analytical methods were able to detect the presence of stimulants and diuretics in the analyzed samples, and in ca. 18% of the samples the caffeine levels were above the maximum recommended daily limit. Hydrochlorothiazide and / or furosemide were found in 12% of the supplement samples. Regarding drug interaction studies, sertraline did not interact pharmacokinetically with caffeine, but increased sildenafil ASC by 72% in the single dose regimen and 138% in the steady state study over the 30 day period.